The Role Of Seating Layout Arrangements In The Kindergarten’s Classroom To Student’s Drawings - Dewi Pramitasari; Diananta Pramitasari (Journal of Architectural Research and Design Studies)
This research aims to identify the correlation between the role of seating layout arrangements and student’s drawings in the kindergarten’s classroom. This kindergarten is located at TK Model, Sleman Regency, D.I. Yogyakarta. This research relates to early childhood learning, so that they can find directions that should be applied in kindergarten’s classroom. This research is also identifies the factors that influence the correlation between the role of seating layout arrangements and student’s drawings, and identify the best area of seating layout arrangement that can optimizing the results of the student’s drawings. This research is using quantitative and qualitative methods. The research uses data and information from the documentation of the activities and student’s drawings as the object of research through questionnaire survey. The data collected shows that there are differences of each type of seating layout arrangements to student’s drawings. The level of the seating layout arrangements and to student’s drawings in this research is a weak correlation. This is because of various factors such as physical and non-physical factors, so that it is refer to design directives that should be applied to optimizing the drawing activities in the classroom. The findings indicate that the use of seating layout arrangement on the floor and carpet by dividing the use area during ongoing activities can be applied. It also shows that physical and non-physical aspects cannot be separated, so it needs a balance between the direction of physical and non-physical aspects based on the sequence of early childhood learning activities carried out by student in the kindergarten classroom.